2015
DOI: 10.3926/ic.557
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of gender on entrepreneurial intentions: A TPB perspective

Abstract: Purpose: To disentangle the ways in which social norms shape entrepreneurial intentions of university students and to analyse the moderating effect of gender that may arise.Design/methodology/approach: We have used the entrepreneurial intention model based on Theory of Planned Behaviour (TPB) literature and moderated by students' gender affecting this intention. We tested some hypotheses using data from undergraduate business students in Spain and their entrepreneurial intentions. Findings:Our results suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 78 publications
6
53
0
Order By: Relevance
“…Women's moderation role is stronger than men (Sanchez-Franco, Ramos, & Velicia, 2009).While according to (Kim, Murrmann, & Lee, 2006) the role of gender moderation (male) is higher than women in the influence of job stress with job satisfaction. Furthermore, gender is proven to moderate the relationship between job stress role with job satisfaction.Then (Robledo et al, 2015) reveals that the effect of gender moderation has a positive effect on women in the relationship between subjective norms and behavioral control over the entrepreneurial intention.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Women's moderation role is stronger than men (Sanchez-Franco, Ramos, & Velicia, 2009).While according to (Kim, Murrmann, & Lee, 2006) the role of gender moderation (male) is higher than women in the influence of job stress with job satisfaction. Furthermore, gender is proven to moderate the relationship between job stress role with job satisfaction.Then (Robledo et al, 2015) reveals that the effect of gender moderation has a positive effect on women in the relationship between subjective norms and behavioral control over the entrepreneurial intention.…”
Section: Resultsmentioning
confidence: 98%
“…The higher the individual intention to perform a behavior, the more likely the individual displays the behavior. TPB has indeed been shown to affect the entrepreneurial intention such as findings (Robledo, Arán, Sanchez, & Molina, 2015) that behavioral control and perceived attitudes affect students entrepreneurial intention, although subjective norms are not proven.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The questionnaires which designed to measure entrepreneurial intention (EI) was adapted from Robledo et al (2015); Linan and Chen (2009), while to measure entrepreneurship education (EE), we adapted items from Denanyoh et al (2015); Opoku-Antwi et al (2012). Furthermore, to understand the entrepreneurial knowledge (EK), we adapted prior instruments validated by Al mamun et al 2017; Kumar et al (2018), whilst to measure entrepreneurial mindset (EM), we applied questionnaires from Mathisen and Arnulf (2013).…”
Section: Instrument Developmentmentioning
confidence: 99%
“…There is a general consensus in the literature about the positive relationship between attitude and EI [ 32 , 33 ]. Ruizalba-Robledo et al [ 34 ] found evidence of such a relationship among potential entrepreneurs in the university context.…”
Section: Literature Reviewmentioning
confidence: 99%